Women Abuse Screening Tool: A Validation Study on Nigerian Pregnant Women (International Journal of Scientific Research and Management (IJSRM), 2020)
Domestic violence is identified across the globe as a menace as it poses a threat to the mental health of its victims, the significant others of the victim and the security of a nation at large. In some cases, the victim of domestic violence is a pregnant woman and harm is caused not only to a woman but her fetus also and this calls for urgent psychological assessment and intervention. Although there is no doubt that psychological tests are effective in the assessment of domestic violence, using the psychometric properties obtained from a different population may produce generate inaccurate findings. This paper therefore attempts the validation study of Women Abuse Screening Tool (WAST) using a sample of 379 pregnant women attending antenatal clinic at the State Specialist Hospital, Osogbo, Osun State, Nigeria. The study derived a Cronbach’s Alpha Reliability of 0.758, p <.05 and a Guttman split-half coefficient of 0.683, p <.05. Furthermore, concurrent validity of Women Abuse Screening Tool (WAST) and Ongoing Abuse Screen (OAS) was established as 0.29, p<.05. The norms of the instrument were given as 2.38 for tolerable level of domestic violence and 5.79 for severe and pathological level of domestic violence. Authors conclude that Women Abuse Screening Tool has acceptable psychometric properties to justify its usage for the assessment of level of domestic violence among pregnant women in Nigeria and other nations with similar socio-cultural backgrounds.